Effects of rare-earth light conversion film on the growth and fruit quality of sweet pepper in a solar greenhouse - Gao, Yaxin; Li, Gongfeng; Cai, Bingbing; Zhang, Ziming; Li, Ning; Liu, Yike; Li, Qingyun (Frontiers in Plant Science, 2022)
Light is an important environmental factor influencing plant growth and development. However, artificial light supplement is difficult to spread for its high energy consumption. In recent years, rare-earth light conversion film (RPO) covering is being focused on to be a new technology to study the mechanism of light affecting plant growth and development. Compared with the polyolefin film (PO), the RPO film advanced the temperature and light environment inside the greenhouse. Ultimately, improved growth and higher yield were detected because of a higher photosynthesis, Rubisco activity and Rubisco small subunit transcription. Compared with that in the greenhouse with polyolefin film, the plant height, stem diameter and internode length of sweet pepper treated with RPO increased by 11.05%, 16.96% and 25.27%, respectively. In addition, Gibberellic acid 3 (GA3), Indole-3-acetic acid (IAA), Zeatin Riboside contents were increased by 11.95%, 2.84% and 16.19%, respectively, compared with that with PO film. The fruit quality was improved, and the contents of ascorbic acid (Vc), soluble protein and soluble sugar were significantly higher than those of PO film, respectively, increased by 14.29%, 47.10% and 67.69%. On the basis of improved fruit quality, the yield of RPO treatment increased by 20.34% compared with PO film. This study introduces an effective and low-energy method to study the mechanism and advancing plant growth in fruit vegetables production.